A bibliometric analysis of research on dementia comorbid with depression from 2005 to 2024 - Li, Xia; Su, Wei; Cai, Lili (Frontiers in Neuroscience, 2025)
IntroductionWith the global rise in life expectancy, the incidence of dementia is increasing, often accompanied by depressive symptoms. Understanding the interplay between dementia and depression is crucial, as depression may not only co-occur with but also potentially exacerbate the progression of dementia. This study employs bibliometric analysis to map the global research landscape, identify prevailing themes, and discern future research directions.MethodsWe analyzed reviews and original research articles on dementia and depression extracted from the Web of Science Core Collection spanning from 2005 to 2024. Utilizing tools such as CiteSpace, VOSviewer, and an R-based bibliometric analysis package, we assessed trends in publication volume, citation frequency, contributing countries, leading institutions, predominant journals, influential authors, and emergent keywords.ResultsA total of 1972 publications were obtained, revealing a consistent increase in both the number of publications and their citation impact over the study period. The United States is the country with the most publications and the most extensive collaborations. The University of Toronto and the Journal of Alzheimer’s Disease were identified as key contributors to this field. This research area is currently focused on cognitive impairments, the role of gut microbiota, and non-drug interventions. Future directions emphasize the importance of early detection and intervention, a deeper understanding of the gut-brain axis, and the integration of technology in treatment strategies. Additionally, there is a growing interest in the physiological and psychological interplays such as oxidative stress and its implications.ConclusionThis study underscores pathogenesis, comorbid conditions, and non-drug interventions as primary research focal points, suggesting these areas as potential pathways for therapeutic innovation. These insights are intended to deepen our understanding, enhance diagnostics, and improve the management of dementia and depression, providing guidance for future research aimed at addressing these escalating global health challenges.